Low molecular weight chitosan-coated silver nanoparticles are effective for the treatment of MRSA-infected wounds - Peng Y (Dove Medical Press, 2017)
Yinbo Peng,1 Chenlu Song,1 Chuanfeng Yang,1 Qige Guo,1 Min Yao1,2 1Department of Burns and Plastic Surgery, Shanghai Ninth People’s Hospital, Institute of Traumatic Medicine, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Department of Dermatology, Wellman Center for Photomedicine, Harvard Medical School, Massachusetts General Hospital, Boston, MA, USA Abstract: Silver nanoparticles (AgNPs) are being widely applied as topical wound materials; however, accumulated deposition of silver in the liver, spleen, and other main organs may lead to organ damage and dysfunction. We report here that low molecular weight chitosan-coated silver nanoparticles (LMWC-AgNPs) are effective against methicillin-resistant Staphylococcus aureus (MRSA), have better biocompatibility, and have lower body absorption characteristics when compared with polyvinylpyrrolidone-coated silver nanoparticles (PVP-AgNPs) and silver nanoparticles without surface stabilizer (uncoated-AgNPs) in a dorsal MRSA wound infection mouse model. LMWC-AgNPs were synthesized by reducing silver nitrate with low molecular weight chitosan as a stabilizer and reducing agent, while PVP-AgNPs were synthesized using polyvinylpyrrolidone as a stabilizer and ethanol as a reducing agent. AgNPs with different surface stabilizers were identified by UV-visible absorption spectrometry, and particle size was determined by transmission electron microscopy. UV-visible absorption spectra of LMWC-AgNPs, PVP-AgNPs and uncoated-AgNPs were similar and their sizes were in the range of 10–30 nm. In vitro experiments showed that the three types of AgNPs had similar MRSA-killing effects, with obvious effect at 4 µg/mL and 100% effect at 8 µg/mL. Bacteriostatic annulus experiments also showed that all the three types of AgNPs had similar antibacterial inhibitory effect at 10 µg/mL. Cell counting kit-8 assay and Hoechst/propidium iodide (PI) staining showed that LMWC-AgNPs were significantly less toxic to human fibroblasts than PVP-AgNPs and uncoated-AgNPs. Treatment of mice with MRSA wound infection demonstrated that the three types of AgNPs effectively controlled MRSA wound infection and promoted wound healing. After continuous application for 14 days, LMWC-AgNPs-treated mice showed significantly reduced liver dysfunction as demonstrated by the reduced alanine aminotransferase and aspartate aminotransferase levels and liver deposition of silver, in comparison to mice treated with uncoated-AgNPs or PVP-AgNPs. Our results demonstrated that LMWC-AgNPs had good anti-MRSA effects, while harboring a better biocompatibility and lowering the body’s absorption characteristics. Keywords: silver nanoparticles, LMWC-AgNPs, MRSA, PVP-AgNPs, PVP, biocompatibility